2010
DOI: 10.1016/j.neuropsychologia.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

More than skin deep: Body representation beyond primary somatosensory cortex

Abstract: The neural circuits underlying initial sensory processing of somatic information are relatively well understood. In contrast, the processes that go beyond primary somatosensation to create more abstract representations related to the body are less clear. In this review, we focus on two classes of higher-order processing beyond somatosensation. Somatoperception refers to the process of perceiving the body itself, and particularly of ensuring somatic perceptual constancy.We review three key elements of somatoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
422
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 423 publications
(443 citation statements)
references
References 206 publications
(190 reference statements)
15
422
2
4
Order By: Relevance
“…Touch, however, can clearly also be used to perceive the extrinsic physical properties of objects. Longo, Azañón, and Haggard (2010) argued that perceiving the metric properties of objects touching the skin requires that immediate sensory signals be combined with (Berryman, Yau, & Hsiao, 2006), sounds produced by action (Tajadura-Jiménez et al, 2012, 2015, the rubber hand illusion (Bruno & Bertamini, 2010), and tool use (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014, 2017. Thus, in analogy with the modulation of perceived passability of apertures when apparent eyeheight was altered shown by Warren and Whang (1987), these results show that experimental manipulations of represented body size alter perceived tactile distance.…”
Section: Statement Of Public Significancementioning
confidence: 87%
“…Touch, however, can clearly also be used to perceive the extrinsic physical properties of objects. Longo, Azañón, and Haggard (2010) argued that perceiving the metric properties of objects touching the skin requires that immediate sensory signals be combined with (Berryman, Yau, & Hsiao, 2006), sounds produced by action (Tajadura-Jiménez et al, 2012, 2015, the rubber hand illusion (Bruno & Bertamini, 2010), and tool use (Canzoneri et al, 2013;Miller, Longo, & Saygin, 2014, 2017. Thus, in analogy with the modulation of perceived passability of apertures when apparent eyeheight was altered shown by Warren and Whang (1987), these results show that experimental manipulations of represented body size alter perceived tactile distance.…”
Section: Statement Of Public Significancementioning
confidence: 87%
“…We used a two-point registration procedure (Bookstein coordinates) to assess localisation biases (as in Azañón et al, 2010;Mancini et al, 2011;Margolis & Longo, 2015). In this procedure, two landmarks are designated as points (0,0) and (1,0), thus defining a twodimensional coordinate system centred on and scaled to the two landmarks (Bookstein, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore alternative explanations of crossing effects that refer to the unfamiliarity of the crossed posture (Azañón et al, 2010b;Longo et al, 2010) or the need for interhemispheric transmission in the crossed posture (Buchholz et al, 2012) seem improbable, given the lack of an influence of hand crossing on touch detection. Further, these alternative explanations do not receive support from our modeling results; our results suggest that crossing effects are not due to posture per se, but, instead, to the anatomical and external response codes being incongruent in crossed, but not in uncrossed postures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether this conflict bears on the remapping process, impairing the establishment of the external response mapping (Yamamoto & Kitazawa, 2001a;Röder et al, 2004;Kóbor et al, 2006;Azañón & Soto-Faraco, 2007;Kitazawa et al, 2008), or whether it unfolds its effect at the stage of information integration once remapping is complete (Shore et al, 2002;Badde et al, 2013;Badde et al, 2015). Additionally, it has been suggested that crossing effects might simply be caused by the additional demands of the unusual, presumably uncomfortable crossed posture (Azañón et al, 2010b;Longo et al, 2010;Haggard et al, 2003) or by additional hemispheric transmission costs, which are specific to the crossed posture (Buchholz et al, 2012;Canzoneri et al, 2014). Furthermore, it has been debated whether crossing effects critically depend on the application of more than one stimulus in the TOJ task (Yamamoto & Kitazawa, 2001a;Kitazawa, 2002;Shore et al, 2002).…”
Section: Introductionmentioning
confidence: 99%